Application of a credit evaluation model in order to reduce the risk of the clients’ portfolio of insurance company - Arce Chíncaro, Eduardo (2011)
This research analyzes a company that belongs to the institutional life subsector of the insurance sector that wants to reduce its credit risks. To do this, the number of policies cancelled after their emission should be minimized. A credit evaluation model has been developed in order to describe and predict accurately the probability that an emission of a policy is profitable for the insurance company. A policy portfolio valued in US$ 10 million with 68,2% of policies retention was used. Using the model an increase of 4,7% in the portfolio value and an increase of 2,9% in the policy retention were gained.